A new approach to the current distribution in field cooled superconductors disks. (24th November 2017) - Bernstein, P; Colson, L; Dupont, L; Noudem, J
Abstract: The Bean model considers that in field cooled superconducting cylinders with diameter R, the currents flow over all the thickness of the superconductor along circular paths, the minimum radius of which depends on the magnetizing field and the critical current density. A combination of trapped field and levitation force measurements reported recently has shown, however, that in YBCO and MgB2 disks the current flows in fact in a restricted region with thickness t of the superconductor. In this contribution, from measurements carried out on two YBCO and two MgB2 disks, we report the dependence on temperature of t and J p, the current density in this region, as well as that of the field trapped by the samples. The results confirm that t decreases as the temperature decreases. This behaviour is ascribed to the conservation of the magnetic energy stored in the superconductor, which depends on the magnetizing source and not on the measurement temperature. As a consequence, t behaves as J p − 2 / 3, while the field trapped along the axis of the cylinder behaves as J p 1 / 3 . These claims are substantiated by the experimental results. The possibility that J p is equal to the depairing current is investigated.